2019
DOI: 10.17576/jsm-2019-4804-05
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Mineralization and Soil Biology as Influenced by Temperature and Fertilizer Management Practices

Abstract: High soil temperature due to climate change may influence nutrient mineralization and soil biology. An incubation study was conducted at Bangladesh Rice Research Institute to determine the effect of temperature (28°C and 45°C) on nutrient mineralization and soil microbial population of two different soils (terrace and saline soil) having different nutrient management practices (chemical fertilizer and integrated nutrient management). Terrace soil was clay loam and saline (6 ds m-1) soil was sandy loam in textu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 37 publications
1
2
0
1
Order By: Relevance
“…This traditional farmland management practice of fertilizer application resulted in the highest TP and AK contents under FL in the present study, which was significantly higher than that under afforestation lands. This was consistent with the findings of Naher et al (2019) in Southeast Bangladesh. Compared with the crops under FL, the trees in LAT and ORO required more TP and AK to support their growth (Deng et al, 2017; Guo et al, 2020), which was also an important reason resulted in the lower TP and AK contents under afforestation lands.…”
Section: Discussionsupporting
confidence: 94%
“…This traditional farmland management practice of fertilizer application resulted in the highest TP and AK contents under FL in the present study, which was significantly higher than that under afforestation lands. This was consistent with the findings of Naher et al (2019) in Southeast Bangladesh. Compared with the crops under FL, the trees in LAT and ORO required more TP and AK to support their growth (Deng et al, 2017; Guo et al, 2020), which was also an important reason resulted in the lower TP and AK contents under afforestation lands.…”
Section: Discussionsupporting
confidence: 94%
“…According to Lai et al (2022) [41], toxic metal pollution produces serious stress on the reproduction and growth of microorganisms in the soil, and the results of microbial abundance showed that the total microbial biomass in toxic metal-contaminated soil was 42.86%, 53.33%, and 44.93% lower than those in non-contaminated soil. Naher et al (2021) [42] find that a higher number of total beneficial bacteria is associated with the highest score of soil quality index, with high OM, moderate pH value, and higher concentration of nutrients. Also, Duarah et al (2011) [43] reported that NPK Fertilization treatments showed a negative effect on the PSBs population, on the other hand, Jana et al (2001) [44] noted that the abundance of PSBs is closely related to C-N and N-P application.…”
Section: Plos Onementioning
confidence: 99%
“…Soil microbial activities are highly reactive to modulation of soil temperature ( Naher et al, 2019 ). Generally, microbial growth and activities are increased under high temperature conditions at a typical temperature range ( Heinze et al, 2016 ).…”
Section: Factors Affecting the Activities Of Ammonia Oxidizersmentioning
confidence: 99%